Pengaruh Penerapan Model Pembelajaran Auditory Intellectually Repetition (AIR) dan Motivasi Terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri 14 Kota Jambi: (The Effect of Applying the Auditory Intellectually Repetition (AIR) Learning Model and Motivation on Learning Outcomes of Class VIII Students of SMP Negeri 14 Jambi City) - Masitah Masitah; Sri Purwaningsih; Jodion Siburian (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
This study aims to determine the effect of using the Auditory Intellectually Repetition (AIR) learning model and motivation on student learning outcomes. The type of research used was quasi-experimental research with a pretest-posttest control group design not randomly. The type of research design used is a 2x2 factorial design. The population in this study were students of grade VIII junior high school first semester. The samples used were class VIII A and VIII C, the samples were taken by purposive sampling technique. Learning achievement data was measured using a learning achievement test and motivational data was measured using a questionnaire. Data were analyzed using two way ANOVA. The results of the analysis show that the difference in post-test scores for the experimental class is higher than that for the control class. Based on the results of the study, it can be concluded that: 1) There is an effect of using the Auditory Intellectually Repetition (AIR) learning model on students' science learning outcomes. 2) There is a motivational influence on students' science learning outcomes. 3) There is no interaction between the use of the Auditory Intellectually Repetition (AIR) learning model and motivation on student learning outcomes. Key words: Auditory Intellectually Repetition (AIR) learning model, motivation and learning outcomes Â ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan model pembelajaran Auditory Intellectually Repetition (AIR) dan motivasi terhadap hasil belajar siswa. Jenis penelitian yang digunakan adalah penelitian eksperimen semu dengan desain penelitian pretest-postest grup kontrol tidak secara random. Jenis rancangan penelitian yang digunakan adalah desain factorial 2x2. Populasi pada penelitian ini adalah siswa kelas VIII SMP semester satu. Sampel yang digunakan adalah kelas VIII A dan VIII C, sampel diambil dengan teknik purposive sampling. Data prestasi belajar diukur dengan menggunakan tes prestasi belajar dan data motivasi diukur dengan menggunakan angket kuesioner. Data di analisis dengan menggunakan ANOVA dua jalur. Hasil analisis menunjukan bahwa selisih nilai post test untuk kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Berdasarkan hasil penelitian maka dapat disimpulkan bahwa: 1) Terdapat pengaruh penggunaan model pembelajaran Auditory Intellectually Repetition (AIR) terhadap hasil belajar IPA siswa. 2) Terdapat pengaruh motivasi terhadap hasil belajar IPA siswa. 3) Tidak terdapat interaksi antara penggunaan model pembelajaran Auditory Intellectually Repetition (AIR) dan motivasi terhadap hasil belajar siswa. Kata kunci: Model pembelajaran Auditory Intellectually Repetition (AIR), motivasi dan hasil Belajar